Konseling Pranikah: Sebuah Upaya Meredukasi Budaya Pernikahan Dini di Kecamatan Pulung Kabupaten Ponorogo - Diana Ariswanti Triningtyas; Siti Muhayati (Universitas Kanjuruhan Malang, 2017)
The long-term goal of this study is to determine the factors that underlie the early marriage and provide understanding to the people of Pulung Ponorogo against the psychological impact of early marriage. To achieve these objectives, the researcher conducted a research entitled: